2012
DOI: 10.1063/1.4753816
|View full text |Cite
|
Sign up to set email alerts
|

Electric field-induced magnetization reversal in a perpendicular-anisotropy CoFeB-MgO magnetic tunnel junction

Abstract: The magnetic Y-branch nanojunction: Domain-wall structure and magneto-resistance Appl. Phys. Lett. 101, 102403 (2012) Kinetics of magnetization processes in a quasi-one-dimensional Ising superantiferromagnet [{CH3}3NH]CoCl3· 2H2O Low Temp. Phys. 38, 843 (2012) Depth-dependent magnetization reversal and spin structure of Fe/NiO exchange-coupled epitaxial bilayers Appl. Phys. Lett. 101, 082412 (2012) Magnetic domain wall induced, localized nanowire reversal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
287
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(297 citation statements)
references
References 22 publications
6
287
4
Order By: Relevance
“…To achieve voltage-induced dynamic magnetization switching of the perpendicularly magnetized free layer, [11][12][13][14] we need to cancel the effective PMA during the switching process; therefore, the sign of the VCMA effect that induces the reduction in PMA is technologically important. In our previous study, we observed a large VCMA coefficient of 290 fJ Vm − 1 in the Cr/Fe/MgO MTJ, as shown by the open circles in Figure 5c.…”
Section: Highly Efficient Voltage Control T Nozaki Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve voltage-induced dynamic magnetization switching of the perpendicularly magnetized free layer, [11][12][13][14] we need to cancel the effective PMA during the switching process; therefore, the sign of the VCMA effect that induces the reduction in PMA is technologically important. In our previous study, we observed a large VCMA coefficient of 290 fJ Vm − 1 in the Cr/Fe/MgO MTJ, as shown by the open circles in Figure 5c.…”
Section: Highly Efficient Voltage Control T Nozaki Et Almentioning
confidence: 99%
“…5,6 The achievement of the VCMA effect in MgO-based MTJs 7 and the demonstration of high-speed responses, such as voltage-induced ferromagnetic resonance (FMR) excitation, 8,9 spin-wave excitation 10 and dynamic magnetization switching, [11][12][13][14] have brought great changes to research in this field. Modulations of the Curie temperature, 15 domain wall propagation, 16,17 interfacial Dzyaloshinskii-Moriya interaction 18 and proximity-induced magnetism 19 have also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to attain this goal have mostly focused on charge accumulation or band shifting in ultrathin ferromagnetic layers with a metal oxide gate dielectric. [15][16][17][18][19][20] In these systems, stable reversal of perpendicular magnetization can be realized when precessional motion of magnetization is triggered by short voltage pulses. 19,20 Giant modulations of PMA have also been obtained by voltage control of oxygen ion migration in metal/metal oxide bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been published on electric-field-controlled magnetic effects in recent years, including magnetic domain wall propagation, 1-8 magnetic phase transitions, [9][10][11][12] spin polarization, 13,14 magnetic anisotropy [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and exchange bias. [33][34][35][36][37] Electric-field control of perpendicular magnetic anisotropy (PMA) would open up new prospects for the realization of high-density magnetic memory and logic technologies operating at low energy consumption levels.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, electrical switching of magnetization direction was realized for a free layer of magnetic tunnel junctions (MTJs) through the change of magnetic anisotropy by applying nanosecond electricfield pulses [5,6]. Most studied MTJs are based on ferromagnetic (FM) metal electrodes and are assembled as ferromagnet/insulator/ferromagnet.…”
Section: Introductionmentioning
confidence: 99%